Correlation between the electrical properties of p-Si/n-4H-SiC junctions and concentrations of acceptors in Si. (16th January 2015) - Nishida, Shota; Liang, Jianbo; Hayashi, Tomohiro; Arai, Manabu; Shigekawa, Naoteru
Abstract: We fabricated p + -, p-, and p − -Si/n-4H-SiC junctions by surface activated bonding (SAB). We investigated their electrical properties by measuring their current–voltage ( I – V ) characteristics at raised ambient temperatures, capacitance–voltage ( C – V ) characteristics at various frequencies, and capacitance–frequency ( C – f ) characteristics at room temperature. The activation energy of their reverse-bias current and the flat-band voltage in their C – V characteristics, which were estimated to be 0.97–1.01 eV and 0.83–0.84 V, respectively, were insensitive to the concentrations of acceptors in Si substrates. The relaxation times estimated from the C – f characteristics were 0.8 and 1.5 µs for the p-Si/n-4H-SiC and p − -Si/n-4H-SiC junctions, respectively. The results are explained by a scheme wherein Fermi level pinning occurs at the Si/4H-SiC interfaces fabricated by SAB.